2014
DOI: 10.1123/tsp.2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Public Expectation, Pressure, and Avoiding the Choke: A Case Study from Elite Sport

Abstract: This case study focused on pressure, stereotype threat, choking, and the coping experiences of the New Zealand All Blacks rugby team during the period from 2004-2011 leading into their success at the 2011 Rugby World Cup (RWC). Employing a narrative approach this case study examined public expectation, pressure, and coach-led coping strategies designed to “avoid the choke” by the All Blacks team. An in-depth interview was completed with one of the All Blacks’ coaches and analyzed via collaborative thematic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Findings revealed five main psychosocial processes underpinning team resilience: transformational leadership (e.g., inspiring team members' commitment to theirshared vision despite setbacks), shared team leadership (e.g., a wide distribution of team member responsibilities), team learning (e.g., sharing knowledge of setbacks), social identity (e.g., developing a distinctive team identity), and positive emotions (e.g., promoting humor despite setbacks). This study illustrated how team resilience processes were essential for the development of excellence which resonates with other research in sport psychology that has identified the critical role of transformational leadership, team leadership, and team identity during challenging situations in elite sport[4,29,30]. Importantly, in both studies conducted by Morgan et al[7,8**], team resilience was portrayed as a dynamic, temporal process.Teams do not exist in static environments[31,32] and these findings suggest that team resilience development should occur in accordance with the stage of a team's existence and the specific stressors encountered in that context and at that time.…”
supporting
confidence: 79%
“…Findings revealed five main psychosocial processes underpinning team resilience: transformational leadership (e.g., inspiring team members' commitment to theirshared vision despite setbacks), shared team leadership (e.g., a wide distribution of team member responsibilities), team learning (e.g., sharing knowledge of setbacks), social identity (e.g., developing a distinctive team identity), and positive emotions (e.g., promoting humor despite setbacks). This study illustrated how team resilience processes were essential for the development of excellence which resonates with other research in sport psychology that has identified the critical role of transformational leadership, team leadership, and team identity during challenging situations in elite sport[4,29,30]. Importantly, in both studies conducted by Morgan et al[7,8**], team resilience was portrayed as a dynamic, temporal process.Teams do not exist in static environments[31,32] and these findings suggest that team resilience development should occur in accordance with the stage of a team's existence and the specific stressors encountered in that context and at that time.…”
supporting
confidence: 79%
“…Athlete-specific factors may precipitate or exacerbate anxiety disorders, including pressures to perform and public scrutiny,7 career uncertainty or dissatisfaction,8 9 and injury 10–12. General psychosocial factors are also strongly implicated in the onset and maintenance of anxiety disorders within the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Despite still existing barriers to applying sport psychology within coaching environments (Newman, 2015;Ravizza, 1988;Weaver, 2014;Winter & Collins, 2015), growing evidence has demonstrated the positive contribution that the field can offer toward achieving enhanced levels of skill learning and performance through a focus on technical issues (e.g., Collins, Doherty, & Talbot, 1993;Hodge & Smith, 2014;Seabourne, Weinberg, Jackson, & Suinn, 1985). It is important to note, however, that if sport psychologists are to make further in-roads within coaching environments, the field must be able to demonstrate even greater expertise in situations relating to the development of an athlete's movement technique (e.g., Mendoza & Schöllhorn, 1993;Penn & Spratford, 2011;Ranson, King, Burnett, Worthington, & Shine, 2009).…”
mentioning
confidence: 99%